Déjà dead - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series., 1997)
A killer in Montreal is murdering and dismembering women, and police are getting nowhere. Forensic anthropologist Temperance Brennan, a middle-aged lady from North Carolina, goes after him herself.